2008
DOI: 10.1080/00016480701596062
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the incudostapedial joint anomaly in conductive deafness

Abstract: Fifteen cases of ossicular anomalies without external ear malformation were studied. The anomaly of the incus-stapes complex was the most frequent. There were two cases of fused incudostapedial (IS) joint, which is an extremely rare occurrence. Case 1 was a 33-year-old man, in whom otosclerosis was suspected and exploratory tympanotomy was performed. The IS joint was fused, and the stapes was immobile. Small fenestra stapedectomy was performed. In case 2, a 52-year-old woman, otosclerosis was also suspected an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Incudostapedial joint dislocation and stapes fixation are the most common anomalies among ossicular malformations (Suzuki et al, 2008). We took a closer look at the middle ear bones in the P3H1 null mice.…”
Section: Resultsmentioning
confidence: 99%
“…Incudostapedial joint dislocation and stapes fixation are the most common anomalies among ossicular malformations (Suzuki et al, 2008). We took a closer look at the middle ear bones in the P3H1 null mice.…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 lists the detailed ossicular chain reconstruction of type Ia (113 cases) in the articles. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] The percentages of patients with deformities in the stapes suprastructure, incus, and malleus were 50.9%, 48.0%, and 18.3%, respectively. Aberrant facial nerves were found in 14 type II patients and 129 type III patients.…”
Section: Literature Review and Statisticsmentioning
confidence: 99%
“…In the present study, our retrospective analysis identified 5 type Ia patients with the missing long process of the incus and poor incudostapedial articulation. A literature search identified 113 type Ia patients (Table 3), which included fixation of the head of the malleus and the body of the incus, synostosis of the malleoincudal articulation, missing long Autogenous incus (30 cases): 1 case, 8 3 cases, 10 6 cases, 14 1 case, 15 19 cases 13 Autogenous (14 cases): 3 cases, 16 5 cases, 13 6 cases 12 Cartilage (5 cases): 5 cases 10 Teflon PORP (9 cases): 2 cases, 6 4 cases, 10 2 cases, 17 1 case 18 Others 9 Teflon TORP (5 cases) (silastic banding) 6 Teflon piston (1 case) 6 Modify cause prosthesis (2 cases) 19 ISJ prosthesis and hydroxyapatite bone cement (1 case) 20 Abbreviations: ISJ, incudostapedial joint; PORP, partial ossicular replacement prosthesis; TORP, total ossicular replacement prosthesis.…”
Section: Type I Mobile Stapes Footplate With or Withoutmentioning
confidence: 99%
“…The incudostapedial joint (ISJ) connecting the incus and stapes in the middle ear significantly affects sound transmission to the cochlea (Funnell et al ., 2005; Zhang & Gan, 2011; Gan & Wang, 2015; Soleimani et al ., 2016; Soleimani et al ., 2017). Pathologies such as disarticulation and ankyloses of the joint are common and may cause hearing loss when vibrations can no longer be efficiently transmitted (Sim & Chang, 2008; Suzuki et al ., 2008). Recent experimental studies have shown that reduced stiffness of the ISJ, caused for example by a separation, could result in decreased stapes vibration at high frequencies (greater than 1 kHz) (Szymanski et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%